13C-metabolic flux analysis of Saccharomyces cerevisiae in complex media - Hayato Fujiwara; Nobuyuki Okahashi; Taisuke Seike; Fumio Matsuda (Metabolic Engineering Communications)
Saccharomyces cerevisiae is often cultivated in complex media for applications in food and other biochemical production. However, 13C-metabolic flux analysis (13C-MFA) has been conducted for S. cerevisiae cultivated in synthetic media, resulting in a limited understanding of the metabolic flux distributions under the complex media. In this study, 13C-MFA was applied to S. cerevisiae cultivated in complex media to quantify the metabolic fluxes in the central metabolic network. S. cerevisiae was cultivated in a synthetic dextrose (SD) medium supplemented with 20 amino acids (SD + AA) and yeast extract peptone dextrose (YPD) medium. The results revealed that glutamic acid, glutamine, aspartic acid, and asparagine are incorporated into the TCA cycle as carbon sources in parallel with glucose consumption. Based on these findings, we successfully conducted 13C-MFA of S. cerevisiae cultivated in SD + AA and YPD media using parallel labeling and measured amino acid uptake rates. Furthermore, we applied the developed approach to 13C-MFA of yeast cultivated in malt extract medium. The analysis revealed that the metabolic flux through the anaplerotic and oxidative pentose phosphate pathways was lower in complex media than in synthetic media. Owing to the reduced carbon loss by the branching pathways, carbon flow toward ethanol production via glycolysis could be elevated. 13C-MFA of S. cerevisiae cultured in complex media provides valuable insights for metabolic engineering and process optimization in industrial yeast fermentation.